Bureaucratic Politics: Blind Spots and Opportunities in Political Science - Brierley, Sarah; Lowande, Kenneth; Potter, Rachel Augustine; Toral, Guillermo (Annual Reviews Inc., 2023)
Bureaucracy is everywhere. Unelected bureaucrats are a key link between government and citizens,between policy and implementation. Bureaucratic politics constitutes a growing share of research in political science. But the way bureaucracy is studied varies widely,permitting theoretical and empirical blind spots as well as opportunities for innovation. Scholars of American politics tend to focus on bureaucratic policy making at the national level,while comparativists often home in on local implementation by street-level bureaucrats. Data availability and professional incentives have reinforced these subfield-specific blind spots over time.We highlight these divides in three prominent research areas: the selection and retention of bureaucratic personnel,oversight of bureaucratic activities,and opportunities for influence by actors external to the bureaucracy. Our survey reveals how scholars from the American and comparative politics traditions can learn from one another. Copyright © 2023 by the author(s).
Keywords: Accountability; Appointments; Bureaucracy; Influence; Lobbying; Oversight; Performance; Personnel; Procurement; 59 Ciencia Política::5902 Ciencias políticas; ODS 10 - Reducción de las desigualdades